Seismic prediction of shale reservoir quality parameters: A case study of the Longmaxi–Wufeng formation in the WY area - Hu, Xiuquan; Yu, Wanli; Yi, Chi; Xiao, Chenjing; Li, Jianghan; Wang, Boqiang (Frontiers in Earth Science, 2023)
Shale is an important natural gas resource that has attracted considerable exploration and development interest globally. China is rich in shale gas resources, which will be the focus of future oil and gas exploration breakthroughs through an increase in reserves and production. The most productive WY shale gas field has the greatest potential for shale gas exploration and development. From the analysis of high-quality shale logging response characteristics, this study examined the drilling logging, seismic, and analytical test data in the WY area. The rock physical model of seismic attribute parameters and shale reservoir quality parameters was established, and the seismic elastic parameters were converted into indicators that directly reflect the quality of shale reservoirs. These indicators include total organic carbon (TOC), high-quality reservoir thickness, porosity, brittleness index, and crack development strength. The results showed that shale reservoir quality parameters have a good correlation with seismic parameters. Corresponding regression equations were established to predict the quality parameters. TOC distribution ranged from 2% to 5% in the study area and was overall high in the north but low in the south. The high-quality shale reserve had a thickness of > 40 m. Except for the northwest region, the porosity was nearly > 4%. The overall brittleness of the study area was preferable, and the brittleness index was > 35%, which is suitable for the formation of network fractures in subsequent fracturing operations. In the study area, the anisotropy of the shale in S1l1I was small, and the overall fractures were underdeveloped. Drilling verifications showed that the prediction results of the quality parameters of the high-quality shale reservoirs were consistent with the actual drilling test results with high reliability. This study provides guidance for the comprehensive prediction of sweet spots and subsequent fracturing and well location deployment.